Impact of Islamic Economic Growth, Financial Literacy, and Inflation on Gini Ratio in Indonesia (2013-2023) - Abizar Al-Ghiffari, Hadraji Mufti; Budi Sekaringsih, Riswanti (Sunan Kalijaga: Islamic Economics Journal, 2025)
This study aims to analyze the effect of Islamic economic growth, financial literacy, and inflation on income inequality in Indonesia as measured by the Gini Ratio during the period 2013-2023. The method used is multiple linear regression and quadratic regression to identify the non-linear relationship between the independent variables and the Gini Ratio. The results show that financial literacy has a significant negative effect on income inequality, while inflation shows no significant effect. Islamic economic growth shows an inverted U shape quadratic relationship, which means that initially an increase in Islamic economic growth increases inequality, but after a certain point it decreases it. These findings suggest the importance of improving people's financial literacy and strengthening an inclusive Islamic economy to promote equitable income distribution in Indonesia.